HUBUNGAN ANTARA POLA ASUH DAN KONSEP DIRI DENGAN PERILAKU LINGKUNGAN MAHASISWA - Agus Priadi (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2017)
The objective of this research was to understand comprehensively about the child’s perception towards parents’ parenting and self-concept with responsibility environmental behavior on college students of academy of management and secretary of BSI in Central Jakarta. It was a quantitative research conducted in a private educational academy in Central Jakarta. The data were collected through participant observation using questionnaire. The data searched by the researcher use correlational approach with survey technique. The data analysis and interpretation indicates that (1)the correlation between child’s perception towards parent’s parenting and responsibility environment behavior on college students are positive and significant with the result of correlation is 0,327.(2) the correlation between self-concept and responsibility environment behavior on college students are positive and significant with the result of correlation is 0,360. Some efforts which have to be done by parents dealing with child’s perception towards parenting are keep communicating with children as many as possible frequently, put trust well on them doing their lives, keep controlling by distance so that parents still understand what they are doing outside, etc. Regarding to self-concept there are many ways to be given to students such as giving training, counselling, put confidence on them, giving them skills well, etc.